Vibration serviceability assessment of the world's longest suspended footbridge in 2020. (October 2022) - Tadeu, António; Romero, António; Dias, Sara; Pedro, Filipe; Brett, Michael; Serra, Miguel; Galvín, Pedro; Bandeira, Filipe
Abstract: This paper investigates the vibrations induced by humans through in situ behaviour tests of the 516 Arouca footbridge (Portugal), the world's longest span in 2020 (516 m). The study consists of in situ experimental tests in which the structure was subjected to wind and pedestrian loads. The bridge is first described, to provide design and construction details, after which its dynamic behaviour is evaluated. The estimated natural frequencies were found to be similar to those previously computed by the finite element method. In addition, modal damping ratios and scaling factors are given. The dynamic responses due to pedestrian loads are then analysed. The damping ratios were found to increase with higher structural response, which highlights the dependence of the damping ratio on the amplitude of the structural response. Pedestrian comfort was evaluated by analysing the amplitudes and accelerations of the vibrations and complemented by applying a survey to the visitors. The results of the in situ tests showed that the bridge can provide users with a challenging and rewarding experience as they cross it, without suffering displacements and accelerations that they might find unnerving.